Напрямки підвищення ефективності процесу подрібнення зернових кормів - Нанка, О. В.; Nanka, Oleksandr (КНТУ, 2015)
Наведені результати аналізу досліджень подрібнення рослинних матеріалів способом різання. Встановлено, що процес подрібнення різанням зернових кормів вивчений недостатньо. Немає єдиної думки про вплив таких параметрів як кут ковзання, вологість та ін. на енергоємність процесу подрібнення. Сформульована фізична постановка задачі фундаментальних теоретичних досліджень подрібнення зернових кормів способом різання. The purpose of this work is results of grinding down of vegetable materials by the method of cutting researches analysis and way of fundamental grinding down of corn forages researches by the indicated method determination. From the physical point of view for solids grinding down there is a process of it is dividing into more or less particles and in spite of plenty of grinding down methods, in it is basis one lies and also the phenomenon is an origin in a body at it is loading of maximum tensions which bring to integrity bodies violation of over and to the laceration of atoms connections and molecules between itself. The grinding down process consists of a few stages: stages of resilient deformation; stages of flowage; own grinding down. As an analysis results of grinding down of vegetable materials researches, in particular stem, it is set a cutting method, that the grinding down of corn forages cutting process is studied not enough. To the present tense there is not the unique idea about influence of such parameters as sliding corner, humidity but other on power-hungryness of grinding down process. Creation of pre-conditions restrains insufficiency of complex of questions of grinding down of corn forage a cutting method for development of new, more effective methods of grinding down on the different stages of this process study. The physical raising of task of fundamental corn forages grinding down is formulated by a cutting method researches.
Directions of increasing grinding down of corn forages efficiency process
Keywords: подрібнення; зернові корми; процес різання; енергоємність; grinding down; corn forages; cutting process; power-hungryness